Innovative approaches to qualitative land assessment and valuation: use of modern technologies and geoinformation x systems - Udovenko, І.; Shemiakin, M.; Likhva, N. (Land Management, Cadastre and Land Monitoring, 2024)
The article examines modern methods and technologies that can be used to increase the accuracy of land valuation. The authors analyze the current problems in the field of rating and offer ways of integrating geoinformation systems with the aim of creating a more objective and information-rich picture of land quality. The purpose of the article. Study of the potential of using the latest technologies and geoinformation systems in determining the quality and classification of land with the intention of increasing accuracy and impartiality in the assessment of land resources. Research methods. During the research, the following methods were used: comparative analysis, the method of automated image decoding, the cartographic method and the geo-information mapping method. The results. The article emphasizes the importance of geoinformation systems in the collection, processing and analysis of data, which allows taking into account a wide range of factors when evaluating land, including erosion processes, soil fertility, ecological status and other critically important indicators. Special attention is paid to the possibilities of using remote sensing and other automated methods for data collection. Conclusions. The results of the research are of practical importance, as they can be used to optimize agricultural management, plan the use of land resources, and develop strategies for their effective use and protection. Prospects for further research may include the development of new algorithms for the analysis and processing of data obtained from satellite images, as well as the improvement of existing geoinformation models for land evaluation. Integration of the obtained models and systems into the practical aspects of land use and agricultural management is also envisaged to optimize the use of land resources and increase the efficiency of land use.
Keywords: land valuation; geoinformation system; geoinformation mapping; ArcGIS PC; GPS measurement; agrochemical monitoring